1-[2-(Carboxymethoxy)phenyl]-N-(4-chlorophenyl)methanimine oxide - Skakle, J.M.S.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
In the title resonance conformer, C(15)H(12)ClNO(4), the central C-N bond [1.297 (2) angstrom] has considerable double-bond character and the N-O bond [1.3215 (18) angstrom] indicates formal negative charge on the oxygen atom. Considerable deviations from co-planarity are evident in the molecule, with both benzene rings twisted out of the central C-C-N-C plane [the dihedral angle formed between the rings = 81.99 (8)degrees]. Similarly, the carboxylic acid residue occupies a position almost normal to the plane of the benzene ring to which it is connected [C-C-O-C torsion angle = -78.42 (17)degrees]. The most prominent intermolecular interactions involve the carboxylic acid the N(+)-O(-) residues with the O-H center dot center dot center dot O hydrogen bonds leading to helical supramolecular chains along the b axis. These chains are connected into layers via C-H center dot center dot center dot O(carbonyl) interactions and the layers are consolidated into the crystal structure by C-H center dot center dot center dot Cl contacts.